Further refinement of Pendred syndrome locus by homozygosity analysis to a 0.8 cM interval flanked by D7S496 and D7S2425. Issue 3 (March 1998) - Mustapha, M; Azar, S T; Moglabey, Y B; Saouda, M; Zeitoun, G; Loiselet, J; Slim, R
Abstract : Pendred syndrome is an autosomal recessive disease characterised by congenital sensorineural deafness and goitre. The gene responsible for Pendred syndrome has been mapped to chromosome 7q31 in a 5.5 centimorgan (cM) interval flanked by D7S501 and D7S523. This interval was recently refined a to 1.7 cM interval located between D7S501 and D7S692. In the present study, we report linkage analysis data on a large consanguineous family genotyped with eight microsatellite markers located between D7S501 and D7S523. Complete cosegregation with the disease locus was observed with the loci analysed, which further supports locus homogeneity for Pendred syndrome and close linkage to this region. Haplotype analysis placed the Pendred syndrome gene between D7S496 and D7S2425 in a 0.8 cM interval. This additional refinement of the Pendred syndrome region will facilitate the construction of a physical map of the region and will help the identification of candidate genes.